A study on customer satisfaction of selected companies on equipment leasing service at Dungun Terengganu / Abuzar Al-Gefari Mat Ramly - Mat Ramly, Abuzar Al-Gefari (2012)
This study is to investigate the customer satisfaction of selected companies on equipment leasing service at Dungun, Terengganu. The first objective of this study is to study the factors that will influence the customer satisfaction to the equipmet leasing service. The second objective is to determine the relationship between independent and dependent variables which are customer service, product quality, security and trust and to determine the most influence dimension toward the customer satisfaction. Descriptive research has been chosen as a research design and the method for data collection for this study is questionnaire. 87 questionnaires have been personally distributed to the selected company that used the equipment leasing services. The distribution process was taken all the operation hours which is from 8.00 a.m until S.OOp.m and from 21st October until 1st November 2012. The analysis of findings in this study consists of frequencies of demographic profile, Reliability analysis, Pearson correlation and Multiple Linear Regression. Lastly is the conclusion and recommendation, researcher will determine which dimension that most contribute to the customer satisfaction and the relationship between customer satisfaction with customer service, product quality and security and trust. The researcher will make the recommendations in this study based on the conclusion and observations.